2004
DOI: 10.1186/bcr788
|View full text |Cite
|
Sign up to set email alerts
|

Tavassoli FA, Devilee P: Pathology and Genetics: Tumours of the Breast and Female Genital Organs. WHO Classification of Tumours series - volume IV. Lyon, France: IARC Press

Abstract: As with all members of the WHO Classification of Tumours series, this book is well presented and represents exceedingly good value for money. In general the quality of production is good, with the photography of high to very high quality with good illustrations and colour balance. Plentiful micro and macroscopic pictures are presented, the latter being particularly helpful in the sections dealing with gynaecological lesions. Unfortunately, in some cases the illustrations are poor, for example fig 1.105c is out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
75
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 4 publications
1
75
0
5
Order By: Relevance
“…Additionally, this report is notable as hamartomas are uncommon and giant types are rare, only representing about 0.7% of benign breast tumours in women 1. It is thought that this figure is low due to underdiagnosis and under-reporting.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Additionally, this report is notable as hamartomas are uncommon and giant types are rare, only representing about 0.7% of benign breast tumours in women 1. It is thought that this figure is low due to underdiagnosis and under-reporting.…”
Section: Introductionmentioning
confidence: 77%
“…Giant breast hamartomas are rare and usually occur in perimenopausal women during the fourth or fifth decades of life 1. However, they can occur at any age with a case reported by Venkatesh and Harish in a 14-year-old girl 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis of primary NET of the breast requires exclusion of NET at non-mammary sites and the presence of histological evidence of intraductal or in situ component [3]. It is a rare entity with a reported incidence of < 1% in postmenopausal females (97%) in the 6th-7th decade of life [1,4,5]. However, Bogina et al have reported neuroendocrine differentiation in 10.4% of breast carcinoma patients in a retrospective analysis of 1232 patients of breast cancer when immunohistochemistry staining was performed with synaptophysin and chromogranin A [6].…”
Section: Discussionmentioning
confidence: 99%
“…Primary neuroendocrine tumour (NET) of the breast is a rare entity and constitutes less than 1% of all breast cancers [1]. The World Health Organization (WHO) defined mammary neuroendocrine carcinoma (NEC) as a separate entity in 2003 and revised the term NEC in 2012 to carcinoma with neuroendocrine differentiation [2].…”
Section: Introductionmentioning
confidence: 99%